Site-Specific Factors Influence the Field Performance of a Zn-Biofortified Wheat Variety - Zia, Munir H.; Ahmed, Iftikhar; Bailey, Elizabeth H.; Lark, R. Murray; Young, Scott D.; Lowe, Nicola M.; Joy, Edward J. M.; Wilson, Lolita; Zaman, Mukhtiar; Broadley, Martin R. (Frontiers in Sustainable Food Systems, 2020)
Background: Biofortification of wheat with zinc (Zn) through breeding and agronomy can reduce Zn deficiencies and improve human health. ‘High-Zn’ wheat varieties have been released in India and Pakistan, where wheat is consumed widely as a dietary staple. The aim of this study was to quantify the potential contribution of a ‘high-Zn’ wheat variety (Triticum aestivum L. var. Zincol-2016) and Zn fertilisers to improving dietary Zn supply under field conditions in Pakistan. Methods: Grain Zn concentration of Zincol-2016 and local reference varieties were determined at three sites of contrasting soil Zn status: Faisalabad (Punjab Province; diethylenetriamine pentaacetate- (DTPA-)extractable Zn, 1.31 mg kg-1 soil; gross plot size 13.3 m2; n=4; reference var. Faisalabad-2008), Islamabad (Capital Territory; 0.48 mg kg-1; 4.6 m2; n=5; reference var. NARC-2011), and Pir Sabak (Khyber Pakhtunkhwa, KPK, Province; 0.12 mg kg-1 soil; 9.1 m2; n=4; reference vars. Pirsabak-2015, Wadhan-2017). Eight Zn fertiliser treatment levels were tested using a randomised complete block design: control; soil (5 or 10 kg ha-1 ZnSO4.H2O; 33% Zn applied at sowing); foliar (0.79 or 1.58 kg of ZnSO4.H2O ha-1 applied as a 250 L ha-1 drench at crop booting stage); three soil  foliar combinations. Results: At the Faisalabad site, the grain Zn concentration of Zincol-2016 was greater than Faisalabad-2008, with no yield penalty. Zincol-2016 did not have larger grain Zn concentrations than reference varieties used at Islamabad or Pir Sabak sites, which both had a lower soil Zn status than the Faisalabad site. Foliar Zn fertilisation increased grain Zn concentration of all varieties at all sites. There were no significant effects of soil Zn fertilisers, or variety·fertiliser interactions, on grain Zn concentration or yield. Conclusions: Environment and management affect the performance of ‘high-Zn’ wheat varieties, and these factors needs to be evaluated at scale to assess the potential nutritional impact of Zn biofortified crops. Designing studies to detect realistic effect sizes for new varieties and crop management strategies is therefore an important consideration. The current study indicated that nine replicate plots would be needed to achieve 80% power to detect a 25% increase in grain Zn concentration.